Reversible Valproate-Induced Subacute Encephalopathy Associated With a MT-ATP8 Variant in the Mitochondrial Genome - De Michele, Giovanna; Sorrentino, Pierpaolo; Nesti, Claudia; Rubegni, Anna; Ruggiero, Lucia; Peluso, Silvio; Antenora, Antonella; Quarantelli, Mario; Filla, Alessandro; De Michele, Giuseppe; Santorelli, Filippo M. (Frontiers in Neurology, 2018)
Introduction. There are several reported cases of patients developing motor and cognitive neurological impairment under treatment with valproic acid (VPA). We describe a woman who developed a subacute encephalopathy after VPA intake, harboring a mitochondrial DNA variant, previously described as causing VPA sensitivity in one pediatric patient. Material and methods. A 65-year old woman developed a progressive, severe neurological deterioration after a three-month treatment with valproate sodium, 800 mg daily. Magnetic resonance spectroscopy (MRS), muscle histochemical analysis and assay of mitochondrial enzymatic activities, and mitochondrial DNA sequencing were performed. Results. Neurological examination showed drowsiness, vertical gaze palsy, inability to either stand or walk, diffuse weakness, increased tendon reflexes. Blood lactate was increased, EEG showed diffuse theta and delta activity, MRI subcortical atrophy and leukoencephalopathy, MRS marked reduction of the NAA spectrum, with a small signal compatible with presence of lactate. Muscle biopsy evidenced presence of ragged red fibers (20%) and reduced COX reactivity. Assay of the muscle enzymatic activities showed multiple deficiencies of the electron transport chain and reduced ATP production. The mt.8393C>T variant in the MT-ATP8 gene was found in homoplasmy. The patient considerably improved after valproate withdrawal. Conclusion. The variant we found has been reported both as a polymorphism and, in a single patient, as related to the valproate-induced encephalopathy. The present case is the first bearing this mutation in homoplasmy. In case of neurological symptoms after starting VPA therapy, once hyperammonemia and liver failure have been ruled out, mtDNA abnormalities should be considered.